New Assessment of Fetal Descent and Forceps Delivery (Springer Singapore, 2018)
This book offers a highly informative guide to forceps devices and delivery techniques. Extensive figures and animations offer readers vivid insights into the fetus station, pelvis, and inserted forceps. The book covers normal presentation and abnormal rotation, presentation and attitudes, and especially focuses on the assessment of fetal descent. It discusses the problem with conventional fetal station, and explains the revised one based on the trapezoidal plane. Instrumental delivery is chosen in cases of worrisome fetal status, protracted labor, or maternal fatigue. Forceps can provides a greater pulling power than vacuum extraction, and the fetus can be delivered in a short time, though this technique calls for experience and technical proficiency. The book argues that in order to ensure safe and reliable forceps delivery, assessment of the fetal station and the site of the largest fetal head circumference is critical. The book offers a new and indispensable reference guide for all obstetricians, not only for residents, but also for all experienced professionals involved in the training of beginners, and even for those using vacuum extraction who would like to assess the fetus more objective and practically.